2010
DOI: 10.1523/jneurosci.4811-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Pattern Analysis of Orientation-Selective Activity in the Primary Visual Cortex

Abstract: Although orientation columns are less than a millimeter in width, recent neuroimaging studies indicate that viewed orientations can be decoded from cortical activity patterns sampled at relatively coarse resolutions of several millimeters. One proposal is that these differential signals arise from random spatial irregularities in the columnar map. However, direct support for this hypothesis has yet to be obtained. Here, we used high-field, high-resolution functional magnetic resonance imaging (fMRI) and multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
210
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(242 citation statements)
references
References 36 publications
30
210
2
Order By: Relevance
“…Post hoc multiple comparisons also showed that regions with radial bias generates the largest LDC, in line with studies by Freeman et al (2013) and Tong et al (2010) which suggested that decoding in the visual cortex is strongly driven by radial bias rather than more fine‐grained response patterns. There was also a numerical trend that improvements due to PMC were stronger in non‐radial‐bias V1 subregions, where the spatial activation patterns may have been expected to be more fine grained.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Post hoc multiple comparisons also showed that regions with radial bias generates the largest LDC, in line with studies by Freeman et al (2013) and Tong et al (2010) which suggested that decoding in the visual cortex is strongly driven by radial bias rather than more fine‐grained response patterns. There was also a numerical trend that improvements due to PMC were stronger in non‐radial‐bias V1 subregions, where the spatial activation patterns may have been expected to be more fine grained.…”
Section: Discussionsupporting
confidence: 87%
“…Visual gratings were chosen as stimuli because their encoding in visual cortical response patterns is reasonably well understood. In particular, we examined the accuracy of multivariate decoding in the primary visual cortex (V1), which is generally high (Alink, Krugliak, Walther, & Kriegeskorte, 2013; Kamitani & Tong, 2005; Tong et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus VTFs were used to evaluate the influence of value (low vs. high) on the orientation selectivity of individual voxels within early regions of visual cortex. This analysis rests on the assumption that the distribution of feature-selective neurons-in this case the distribution of orientation-selective columns-is not uniform across a given visual area (Boynton 2005a;Kamitani and Tong 2005;Swisher et al 2010). Due to this nonuniform distribution of neural selectivity, a given voxel may contain more neurons tuned to one particular orientation, giving rise to a Gaussian-shaped response profile across orientations, which we refer to as the VTF (Serences et al 2009; see also Kamitani and Tong 2005;Kay et al 2008;Miyawaki et al 2008).…”
Section: Analysis Of Feature-selective Vtfs In Each Roimentioning
confidence: 99%
“…If orientation decoding really depends on fine-scale variability in the distribution of columns, it is unclear how this signal could still be detected when blurred via smoothing. Swisher et al (2010) attempted to resolve this question regarding the scale of representation that contributes to a successful orientation classification by testing classification performance with high-resolution fMRI in cats (9.4 T) and humans (7 T) who viewed oriented gratings. In the fMRI data, the authors considered classification performance by applying high-or low-pass spatial filters, enabling them to determine the contribution of different spatial scales to successful multivariate classification analysis.…”
mentioning
confidence: 99%